1989
DOI: 10.1111/j.1471-4159.1989.tb07347.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on K+‐Induced Cytosolic Ca2+ Changes in Rat Cortical Synaptosomes

Abstract: 45Ca2+ uptake and cytosolic Ca2+ concentrations [( Ca2+]i) were measured in synaptosomes prepared from the cerebral cortex of 3-, 16-, and 24-month-old male Charles River Wistar rats. Electron-microscopic examination demonstrated no morphological differences between the synaptosomes prepared from 3- and 24-month-old rats. The fast phase of Ca2+ uptake was reduced in the 24-month-old animals as compared to the 3-month-old ones (-23%, p less than 0.001), whereas no difference was found between the 16- and the 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Although it has been consistently demonstrated that calcium homeostasis is perturbed in the neurons of aged animals, the degree and/or direction of change depends on the structure examined and the method of evaluation used. For example, elevated resting levels of neuronal calcium, increased density of L-type calcium channels, and prolonged decay of calcium signals have been reported (Martinez et al 1988;Giovannelli and Pepeu 1989;Verkhratsky et al 1994;Villalba et al 1995;Thibault and Landfield 1996;Toescu and Verkhratsky 2000). These alterations in neuronal calcium homeostasis may yield a shift in the phosphatase-kinase ratio required for proper working memory function (Fig.…”
Section: Potential Substrates Contributing To Working Memorymentioning
confidence: 99%
“…Although it has been consistently demonstrated that calcium homeostasis is perturbed in the neurons of aged animals, the degree and/or direction of change depends on the structure examined and the method of evaluation used. For example, elevated resting levels of neuronal calcium, increased density of L-type calcium channels, and prolonged decay of calcium signals have been reported (Martinez et al 1988;Giovannelli and Pepeu 1989;Verkhratsky et al 1994;Villalba et al 1995;Thibault and Landfield 1996;Toescu and Verkhratsky 2000). These alterations in neuronal calcium homeostasis may yield a shift in the phosphatase-kinase ratio required for proper working memory function (Fig.…”
Section: Potential Substrates Contributing To Working Memorymentioning
confidence: 99%
“…However, there has been some controversy on this subject. Some studies, which were based on 45Ca measurements, reported decreased calcium uptake with aging (Peterson and Gibson, 1983;Leslie et al, 1985;Vitorica and Satrustegui, 1986;Giovannelli and Pepeu, 1989). In those studies, net calcium uptake was observed, where ionic calcium concentration and deposited calcium in organelles were not separately determined.…”
Section: Reduced Calcium Influx Into Aged Synapses Evoked By Depolarimentioning
confidence: 99%
“…As the voltage-dependent calcium influx is thought to be a prerequisite for activating the series of reactions leading to exocytosis and ACh release, calcium influx should be examined as the first step. Many studies using radiolabeled calcium have indicated decreased calcium influx into synaptosomes from aged rodents (Peterson and Gibson, 1983;Leslie et al, 1985;Victorica and Satrustegui, 1986;Giovannelli and Pepeu, 1989). It was not clear from these studies, however, whether the calcium uptake by the intrasynaptosomal mitochondria was taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…1998). Synaptosomes from brains of aged rats demonstrated elevated resting levels and a slower decay in depolarization‐induced Ca 2+ transients than similar preparations from younger animals (Giovannelli and Pepeu 1989; Satrustegui et al. 1991; Michaelis et al.…”
mentioning
confidence: 99%
“…We have previously shown that both the activity and protein levels of PMCA are progressively reduced in synaptic plasma membranes (SPMs) with increasing age in both F344 and F344/BNF1 rats (Michaelis et al 1984(Michaelis et al , 1996Zaidi et al 1998). Synaptosomes from brains of aged rats demonstrated elevated resting levels and a slower decay in depolarization-induced Ca 2+ transients than similar preparations from younger animals (Giovannelli and Pepeu 1989;Satrustegui et al 1991;Michaelis et al 1992). The activity of PMCA is regulated by the Ca 2+ -binding protein CaM, and the amount of CaM tightly associated with SPMs is also markedly reduced in membranes from aged rat brain (Zaidi et al 1998).…”
mentioning
confidence: 99%